(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article presents data on patients with cholelithiasis in the Bukhara region who applied to the Bukhara branch of the RSCEA in 2021 and 2022. First, after obtaining clinical and anamnestic data, patients admitted to the emergency department were diagnosed and treated with instrumental methods and laboratory methods. Among the treatment measures, outpatient care, conservative inpatient and surgical methods were used. This information contains information about medical procedures performed in 2021 and 2022 in the 1st surgical department of the Bukhara branch of the RSCEA.